Revisiting the Fiqh of halal-haram animals: An analysis on Malaysian fatwa relating to animal care and use - Mokhtar, M.I.; Munir, S.M.I. (2017)
The recent trends in the field of scientific research welcomes the interpolation of alternative research ideologies and methodologies in ensuring that issues advocating the Animal Care and Use (ACU) be handled in an ethical and holistic manner. This research tends to provide a connection between conventional animal ethics and Islamic ethics as a complementary framework via the application of Fiqh halal-haram animals. The gist of discussion in this paper is based on the Malaysia context. This exploratory research invokes an exhaustive referencing of voluminous Islamic literature primary resources and in-depth interviews with four renowned Muftis. The number of Fatwas related to the ACU according to the States in Malaysia so far is Kelantan 33, Federal Territory 25, Selangor 17, Terengganu 12, Negeri Sembilan 8, Pahang 8, Perlis 3, Penang 3 and Sarawak 3. 1t can be concluded that the care and use of animals essentially in the keeping of goodness (Jalb ul-masalih) and avoidance of destruction (Dar ul- mafasid) towards religion, life, intellect, lineage and property are permissible. In considering the ethical inquiries in animal care and use, this study found that it needs to be integrated with scientific information as well as religious teachings.